Changes in composition of essential oils and volatile emissions of Minthostachys mollis, induced by leaf punctures of Liriomyza huidobrensis - Banchio, Erika (2007)
Plant defensive mechanisms against herbivores include chemical changes following damage. Effects of feeding punctures produced by Liriomyza huidobrensis (pea leafminers) adult females on the plant’s dominant monoterpenes, pulegone and menthone were assessed by monitoring essential oil composition at 24, 48, and 120 h; emission of volatiles was also measured 24 and 48 h after wounding. We studied such changes in Minthostachys mollis, a Lamiaceae species native to Central Argentina with medicinal and aromatic uses. Leaf puncturing resulted in reduced menthone throughout the experiment and increased pulegone concentration in M. mollis essential oil during the first 48 h. The adjacent undamaged leaves showed similar changes, suggesting a systemic response. Composition of volatiles released from damaged leaves was also altered, most noticeably by increasing pulegone and diminishing menthone emissions. Such herbivore-induced chemical changes in aromatic plants are economically relevant, since the quality of essential oils and volatile emissions are altered.